ABCG2 as a therapeutic target candidate for gout. (1st February 2018) - Fujita, Kyoko; Ichida, Kimiyoshi
ABSTRACT: Introduction : Hyperuricemia (chronically elevated serum uric acid) is the main pathology underlying the development of gout, the most common inflammatory arthropathy. Management of these conditions therefore relies on controlling serum uric acid levels. ATP-binding cassette transporter, sub-family G, member 2 (ABCG2/BCRP) is a well-studied urate transporter expressed on apical membranes in several tissues, including the intestine, liver, and kidney. Here, we discuss the potential of future gout therapies targeting ABCG2. Areas covered : ABCG2 regulates serum uric acid via physiologically important roles in both renal and extra-renal urate excretion. ABCG2 dysfunction, which promotes onset of hyperuricemia, often results in decreased urate excretion through the extra-renal (principally intestinal), rather than the renal pathway. This review covers recent attempts to establish the basis of ABCG2 function according to genetic diathesis, its molecular structure, and the effects of medication. Furthermore, the possibility of treating gout and hyperuricemia by upregulating intestinal ABCG2 expression is examined. Expert opinion : ABCG2 holds great promise as a therapeutic target for these conditions, particularly considering its involvement in extra-renal urate excretion. Manipulation of ABCG2, including controlling the level and location of its expression, has the potential to prevent gout by promoting uric acid excretion as effectively as general uricosuric drugs. Abbreviations : ATP-binding cassette (ABC), transmembrane domain (TMD), nucleotide binding domain (NBD), single nucleotide polymorphism (SNP), single nucleotide polymorphisms (SNPs).